On coxeter functors for some classes of algebras generated by idempotents - Kruhlyak, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We study properties of annihilation operators of infinite order that act in spaces of test functions. The results obtained are used for establishing the coincidence of spaces of test functions.